Aqueous methanol to formaldehyde and hydrogen on Pd/TiO2 by photocatalysis in direct sunlight: structure dependent activity of nano-Pd and atomic Pt-coated counterparts - Nalajala, Naresh; Salgaonkar, Kranti N.; Chauhan, Inderjeet; Mekala, Siva Prasad; Gopinath, Chinnakonda S. (ACS Applied Energy Materials, 2021)
In the present investigation, facet-controlled Pd nanoparticles with nanocube (Pd-NC) and truncated octahedron (Pd-TO) morphologies, and their counterparts with half-a-monolayer of atomic Pt coated (0.5 theta(Pt)-Pd-NC and 0.5 theta(Pt)-Pd-TO) surfaces were prepared. All of them were characterized and evaluated as cocatalyst after supporting them on commercial titania (P25) (Pd-NC/P25, Pd-TO/P25, 0.5 theta(Pt)-Pd-NC/P25, and 0.5 theta(Pt)-Pd-TO/P25) under direct sunlight and/or one sun conditions for the oxidation of methanol to formaldehyde along with solar hydrogen production. Pd-NC/P25 shows higher activity for hydrogen generation compared to Pd-TO/P25; however, activity reversal occurs with the above cocatalysts, but, after Pt-coating with further enhanced activity. The highest conversion of methanol (0.2 mu mol/h.mg) to 100% selective formaldehyde was observed with 0.5 theta(Pt)-Pd-TO/P25, while other catalysts show significantly lower methanol conversion in the following order: 0.5 theta(Pt)-Pd-TO/P25 > 0.5 theta(Pt)-Pd-NC/P25 > Pd-NC/P25 > Pd-TO/P25. Pt-coated on (111) facets of Pd-TO simulates the activity associated as that of Pt(111) facets and demonstrating the highest and facet dependent activity. The present study is truly in resonance with exploiting the surface properties for heterogeneous catalysis, and highlights that less than a monolayer of Pt is sufficient to simulate the activity as that of bulk Pt. It is worth exploring this concept to other metals and substrates too.
Keywords: heterogeneous catalysis; Nanomaterials; Oxidation; Photocatalysis; surface modification